Pengaruh Pendekatan Keterampilan Proses terhadap Hasil Belajar IPA Siswa di Sekolah Dasar - Ratri Shinta Wardhani; Siwi Utaminingtyas; Novy Trisnani (Bima Journal of Elementary Education, 2023)
This research aims to empirically determine whether the use of the process skills approach has an influence on the science learning outcomes of fourth-grade students at SDN in the Kulon Progo region. The research is of an experimental type and was conducted at SDN Kulon Progo, specifically in the fourth-grade classes. The sample was selected using Cluster Random Sampling technique. Data collection was done using a learning outcome test as the instrument, which consisted of only objective multiple-choice questions totaling 30 items. The normality test using the Lilliefors test indicated that both classes had a normal distribution. Subsequently, a homogeneity test was conducted, showing that both classes were homogeneous. The data was then analyzed using a t-test for hypothesis testing. The calculation results showed that the calculated t-value was 3.82, while the tabulated t-value at a significance level of α = 0.05 was 1.67. This means that the null hypothesis (Ho) was rejected, and the research hypothesis (H1) was accepted. Therefore, it can be concluded that there is a significant influence of the use of the process skills approach on the science learning outcomes of fourth-grade students in Kulon Progo